Multisectoral coordination during the COVID-19 pandemic: practices, challenges and recommendations for future preparedness—a systematic literature review protocol - Themba Ginindza; Javan Solomon Okello; Julius N Odhiambo (BMJ Open)
Introduction The COVID-19 pandemic amplified the need for robust multisectoral coordination; yet the specific mechanisms, benefits and challenges of such collaboration particularly in low- and middle-income countries (LMICs) remain poorly synthesised. This review aims to delineate the key elements, benefits, challenges and improvement strategies of multisectoral coordination during COVID-19 and to compare patterns between LMICs and high-income countries (HICs).Methods and analysis Eligible studies will include empirical qualitative, quantitative or mixed-methods research published in English between 1 January 2020 and 15 August 2024 that examines formal coordination mechanisms (eg, task forces, public-private partnerships, inter-agency committees) within the context of COVID-19. Searches will be conducted across PubMed, EBSCOhost, Emerald Insight, Google Scholar and selected grey-literature repositories. Citation chaining will be employed to identify additional sources.Two reviewers will independently screen all records using Covidence, applying pre-piloted eligibility criteria to 5% of citations and proceeding only if inter-rater reliability achieves κ≥0.70. Data will be extracted into a Consolidated Framework for Implementation Research (CFIR)-informed template. Qualitative data will be analysed through framework synthesis, structured by the five CFIR domains. Quantitative data will be narratively summarised and, where outcomes are sufficiently similar across at least two studies, synthesised using a fixed-effect model.Risk of bias will be assessed using Critical Appraisal Skills Programme for qualitative and Risk Of Bias In Non-randomised Studies of Interventions for non-randomised studies. Studies with serious or critical risk will be excluded from pooling. Subgroup analyses (LMIC vs HIC), sensitivity analyses (model and risk) and confidence grading using Confidence in the Evidence from Reviews of Qualitative Research and Grading of Recommendations, Assessment, Development and Evaluations will be conducted.Ethics and dissemination No primary data will be collected; thus additional Research Ethics Committee approval is unnecessary. The results will be disseminated via open-access publication, conference presentations and policy briefs for Nairobi County health stakeholders.PROSPERO registration number CRD42023466849.